¿Los medios promueven una opinión pública deliberativa sobre la criminalización internacional de la droga?. Análisis de contenido en El Tiempo y El Espectador = Does the media promote deliberative public opinion on international drug criminalization?. Content analysis in El Tiempo and El Espectador (2017)
This article is concerned with the role of the media in the formation of a deliberative public opinion. deliberative public opinion, investigating whether the way in which the Colombian media have dealt with the issue of international drug criminalization favors the formation of this type of public opinion. formation of this type of public opinion. The current state of international drug policy and the international drug policy and the configuration of the criminalization discourse are contextualized. A content analysis of 802 news and informative articles in El Tiempo and El Espectador is carried out. Tiempo and El Espectador, taking into account the tendency they presented with respect to the two approaches to international drug policy. the two approaches to international drug policy: the war on drugs and public health. war on drugs and public health